Experimental evaluation of model predictive current control for a modified three-level four-leg indirect matrix converter - Basri, Hazrul Mohamed; Mekhilef, Saad (Institution of Engineering and Technology, 2018)
This study presents an experimental validation and robustness evaluation of predictive current control and reactive power minimisation strategy for a three-level three-phase four-wire indirect matrix converter. The proposed topology features a unification of conventional four-leg indirect matrix converter with an additional four switches circuit resembling a back-to-back buck circuit to synthesise multi-level variable dual dc-link voltage. A systematic rectifier switching strategy is elaborated to ensure positive fictitious dc-link voltage at any instant. The proposed control and topology have been tested under various transient and steady-state conditions for comprehensive robustness evaluation. The experimental results reveal an outstanding independent load current reference tracking with low ripple current and the reactive power minimisation has been achieved by tuning the weighting factor. The load current tracking and reactive power minimisation have been achieved by properly tuning the weighting factor. The load current harmonics distortion is recorded < 5% during normal operating conditions.